Toward a common component architecture for high-performance scientific computing - Armstrong, R.; Gannon, D.; Geist, A.; Keahey, K.; Kohn, S.; McInnes, L.; Parker, S.; Smolinski, B. (Proceedings of the IEEE International Symposium on High Performance Distributed Computing, 1999)
Describes work in progress to develop a standard for interoperability among high-performance scientific components. This research stems from the growing recognition that the scientific community needs to better manage the complexity of multidisciplinary simulations and better address scalable performance issues on parallel and distributed architectures. The driving force for this is the need for fast connections among components that perform numerically intensive work and for parallel collective interactions among components that use multiple processes or threads. This paper focuses on the areas we believe are most crucial in this context, namely an interface definition language that supports scientific abstractions for specifying component interfaces and a port connection model for specifying component interactions.